Will the Obama administration change tack on protectionism before things get worse? - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
The new American government under President Barrack Obama is not the biggest cheerleader for free trade. With its own domestic economy entering this steep downturn, talks of protectionism in one form or another have been voiced every now and then. Catchy buzzwords like “Buy America” are gaining traction. The temptation to turn inwards, driven by the obligation to votes is growing stronger.